Influence of animal-, environment-, and management-related factors on grazing behavior and performance of rangeland beef heifers - Continanza, Fatima Guadalupe (2019)
Tesis para obtener el grado de Doctor of Philosophy, presentada en la New Mexico State University (Estados Unidos), en noviembre de 2019.